Laparoscopic repair of primary unilateral inguinal hernia is it to pamper the ego of the surgeon - Kalyanasundar, Suresh; Bandi, Pradeep Kumar (International Surgery Journal, 2017)
Background: The study compared the procedure of open Lichtenstein tensionless repair of primary unilateral incomplete uncomplicated inguinal hernia with laparoscopic preperitoneal repair by TEP in a rural secondary level hospital for plantation workers. The aim of the study was to compare both the procedures and if laparoscopic repair had any specific advantage over the conventional open repair with specific relation to time of return to work, recurrence and cost effectiveness of the procedures. Methods: This was a prospective study involving 200 cases which were detected and operated between 2006 and 2014 at our hospital and subsequently followed up till 2016 which is 2 years. The patients selected were plantation workers. Results: In all 200 cases got enrolled in the study 100 underwent open tensionless Lichtenstein repair and 100 of them underwent Laparoscopic repair-TEP. Conclusions: Primary unilateral uncomplicated incomplete inguinal hernia repaired by laparoscopic method has no distinct advantage with reference to return to work recurrence of hernia and the cost involved is more as compared to open Lichtenstein repair.